2000
DOI: 10.1038/sj.jp.7200392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transfusion on Hemoglobin Variants in Preterm Infants

Abstract: OBJECTIVE:To determine the effect of transfusion on hemoglobin (Hb) variants in very low birth weight infants and to correlate these changes with parameters measured in routine complete blood counts. METHODS:Hb variants were measured by capillary isoelectric focusing on 126 specimens from 25 very low birth weight infants during their hospital course. These results were compared with transfusion frequency, mean corpuscular volume (MCV), and red cell distribution width. RESULTS:Mean initial Hb F level before tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Preterm birth is associated with an abrupt and early transition to ex utero environment, with blood oxygen saturation levels increasing rapidly from physiological fetal levels (45%–55%) to adult values 23. Early exposure to higher oxygen concentrations, neonatal oxygen supplementation and repeated adult red blood cell transfusions that result in a transition from fetal to adult haemoglobin predominance (with a different O 2 affinity) in early life24 may durably alter oxygen-sensing pathways in preterm neonates that could result in a long-term upregulation of erythropoiesis in individuals born preterm. Since red blood cell transfusions in the neonatal period and duration of neonatal oxygen supplementation were associated with each other, the observational nature of our study does not allow to distinguish the effects of these factors separately.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth is associated with an abrupt and early transition to ex utero environment, with blood oxygen saturation levels increasing rapidly from physiological fetal levels (45%–55%) to adult values 23. Early exposure to higher oxygen concentrations, neonatal oxygen supplementation and repeated adult red blood cell transfusions that result in a transition from fetal to adult haemoglobin predominance (with a different O 2 affinity) in early life24 may durably alter oxygen-sensing pathways in preterm neonates that could result in a long-term upregulation of erythropoiesis in individuals born preterm. Since red blood cell transfusions in the neonatal period and duration of neonatal oxygen supplementation were associated with each other, the observational nature of our study does not allow to distinguish the effects of these factors separately.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological content of hemoglobin F (HbF) of over 90% in that period of life is replaced by HbA, resulting in a dissociation curve shift, which can be responsible for oxygen toxicity [7,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that after five transfusions in infants, the hemoglobin F (HbF) level declines to below 15% of the total hemoglobin, compared with 87.1±5.1% before transfusion [12]. This change affects the hemoglobin oxygen dissociation curve and results in increased oxygen toxicity during this period of life [13,14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A convenient CIEF system applying the standard two-step CIEF technique with pressure mobilization was used to analyze both Hb and globin chain variants [36][37][38]. The isoelectric points of the hemoglobin variants were determined and used for identification in CIEF applying external standards [39].…”
Section: Hemoglobinmentioning
confidence: 99%